2021
DOI: 10.3390/jcm10091844
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Diseases and COVID-19 as Risk Factors for Poor Outcomes: Data on 13,940 Hospitalized Patients from the Spanish Nationwide SEMI-COVID-19 Registry

Abstract: (1) Objectives: To describe the clinical characteristics and clinical course of hospitalized patients with COVID-19 and autoimmune diseases (ADs) compared to the general population. (2) Methods: We used information available in the nationwide Spanish SEMI-COVID-19 Registry, which retrospectively compiles data from the first admission of adult patients with COVID-19. We selected all patients with ADs included in the registry and compared them to the remaining patients. The primary outcome was all-cause mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…These studies include a Danish and Spanish national registry study that both observed similar COVID-19-related mortality rates for patients with rheumatic diseases and the general population. 3 4 This is in line with our own data, as we observed low absolute numbers of patients with rheumatic diseases that were admitted to the ICU or who died (n=3), although we were unable to estimate relative risks due to these low number and absence of controls who required ICU admission. In contrast, we observed that COVID-19-related hospitalisation rates were higher in patients compared with controls (7% vs 1%), especially in patients treated with B-cell targeting therapy (42%).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These studies include a Danish and Spanish national registry study that both observed similar COVID-19-related mortality rates for patients with rheumatic diseases and the general population. 3 4 This is in line with our own data, as we observed low absolute numbers of patients with rheumatic diseases that were admitted to the ICU or who died (n=3), although we were unable to estimate relative risks due to these low number and absence of controls who required ICU admission. In contrast, we observed that COVID-19-related hospitalisation rates were higher in patients compared with controls (7% vs 1%), especially in patients treated with B-cell targeting therapy (42%).…”
Section: Discussionsupporting
confidence: 87%
“…Registry studies that have assessed severe COVID-19 outcomes (eg, ICU admission or death) in a population that was hospitalised due to COVID-19 avoided using these (possibly) biased incidence rates, and may therefore provide more accurate risk estimates for severe COVID-19 manifestations. These studies include a Danish and Spanish national registry study that both observed similar COVID-19-related mortality rates for patients with rheumatic diseases and the general population 3 4. This is in line with our own data, as we observed low absolute numbers of patients with rheumatic diseases that were admitted to the ICU or who died (n=3), although we were unable to estimate relative risks due to these low number and absence of controls who required ICU admission.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the manual search of gray literature and preprints, 18 potentially related papers were included. After reviewing the titles and abstracts of the articles, 157 peer-reviewed papers or preprinted manuscripts were reviewed and a total of 91 articles were entered into the present meta-analysis [ 8 , [14] , [15] , [16] , [17] , [18] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] ,…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports suggested association of biologic DMARDs with severe COVID-19 outcome [ 11 , 12 , 36 , 38 40 ],; however, the relationship of biologic DMARDs or JAK inhibitor usage with COVID-19 outcomes is not clear currently. A report from the first 600 cases from the C19-GRA physician-reported registry suggested that the use of tumour necrosis factor (TNF) inhibitors may reduce the probability of hospitalisation [ 11 ].…”
Section: Discussionmentioning
confidence: 99%